O papel do BRICS na mudança de conjuntura do Sistema Internacional contemporâneo - Ferreira, Marina Velloso (2024)
The purpose of this essay is to analyze and understand the role currently played by the BRICS within the international system, by analyzing its formation, rise, transformation and future prospects. The question that guides this research is: “What role does the BRICS play, especially in terms of the prominence given to the Global South, in changing the conjuncture of the contemporary international system?”. In order to answer it, various secondary and primary sources are used, such as journalistic and academic articles, books, thesis, speeches and declarations by heads of state and foreign ministers, in order to explore how the BRICS and its entities relate to the actors and the current context of the international order. This thesis is built around a case study structured in three parts: introduction, development of the thesis and conclusion. The introductory text briefly introduces the subject of this study, proposing the question that will guide this analysis. The development of this thesis is divided into three chapters: the first is an expositive text, centered around a description of the origin and evolution of the BRICS; the second chapter deals with empirical perspectives, based on International Relations theories, about the debates concerning the international order; the third chapter, in turn, expands the thesis of this study, empirically exploring the role played by the group in the future of the international order. Finally, this thesis concludes that BRICS is a key player in the struggle for a fairer international system, in which the Global South has alternatives to the impositions of the great powers of the Global North.